Emerging Adult Siblings of Individuals with Schizophrenia: Experiences with Family Crisis. (November 2020) - Graves, Jillian M.; Marsack-Topolewski, Christina N.; Shapiro, Janet
The developmental process of siblings of individuals with schizophrenia can be complicated due to crises, as well as numerous individual and familial changes. This qualitative study uses grounded theory techniques to analyze the lived experiences of emerging adult siblings (ages 18–30 years) of individuals with schizophrenia. We conducted 23 one-on-one intensive interviews with sibling participants, using open-ended questions and prompts. Based on the results of the analysis, themes emerged from interview responses related to the influence of the family's coping style during times of crisis and the quality of the family relationships. Findings suggested that parental attunement was correlated with relational closeness in the family, even if parents struggled to master the tasks related to crisis management. To assist siblings and their families in maintaining relationships and to assist with coping, practitioners need to support families around developing developmentally sensitive coping techniques that include all members of the family.